Today's Cutting Edge is Tomorrow’s Obsolete: An Interview with Cory Arcangel and Tina Kukielski - Benjamin Ogrodnik (Contemporaneity: Historical Presence in Visual Culture, 2014)
Exhibited at the Carnegie Museum of Art, Pittsburgh from November 3, 2012 to January 27, 2013, Cory Arcangel: Masters was a wide-ranging, multi-sensory survey of the artist’s major works to date. The following interviews with Arcangel and the exhibition’s curator Tina Kukielski were conducted in February 2013, and discuss the conceptual, curatorial, and aesthetic issues raised by the exhibition.